Connections between Children's Eating Habits, Mental Health, and Parental Stress - Marco Tommasi; Francesca Toro; Alessandra Salvia; Aristide Saggino (Hindawi Limited, 2022)
Background. Obesity and eating disorders are increasing in occidental countries and can undermine physical and psychological health. Therefore, preventing the insurgency of unhealthy eating habits in childhood is fundamental. Parents can play an important role in assisting pediatricians, psychiatrists, and clinical psychologists in the diagnosis of eating disorders because they have an active role in observing and assessing the quality of their children's eating habits. Methods. In our study, we collected data from a sample of children (n = 125) and their parents (n = 161) without symptoms related to eating disorders. Parents assessed the eating habits, behavior problems, and mental health of their children and parental stress. In addition, we measured body mass index, anxiety, and lifestyle in children. Data were analyzed with bivariate correlation and MIMIC models. Results. Both mothers' and fathers' assessments of children's eating habits are reliable. Unhealthy eating habits are connected with children's behavioral problems and parental stress. We did not find significant differences in feeding styles and ways of assessing the quality of eating habits between mothers and fathers. Our study showed greater sensitivity of mothers toward the physical fitness of their children rather than fathers. Conclusions. Mothers and fathers both proved to be good observers of their children's eating behavior, and they could cooperate with medical and psychological operators in preventing the risk of obesity.